Gastrointestinal Complaints and Correlations with Self-Reported Macronutrient Intake in Independent Groups of (Ultra)Marathon Runners Competing at Different Distances - Daan Hoogervorst; Nancy van der Burg; Joline J. Versteegen; Karin J. Lambrechtse; Martijn I. Redegeld; Larissa A. J. Cornelissen; Floris C. Wardenaar (MDPI AG, 2019)
This study investigated the differences in gastrointestinal (GI) and exercise related complaints between groups of runners competing at different distances using web-based questionnaires. Total (severe) complaints were reported by 89.3% (49.7%) of the runners during the race vs. 70.6% (29.4%) after the race. Significant differences between groups were described for marathon (n = 98) and 60 km (n = 43) runners. During competition, runners reported the urge to urinate (47.7%), muscle cramps (43.6%) and belching (43.6%). The prevalence of bloating, flatulence, side ache and dizziness differed between distances (p < 0.02). There were small to moderate negative correlations between food and fluid intake and GI complaints. After competition (12 h), 70.6% of participants reported complaints, with muscle cramps (47.6%), flatulence (19.0%) and bloating (12.7%) being the most prevalent. Prevalence of belching, nausea, stomach cramps and muscle cramps differed between race distances (p < 0.04). There were small to high positive correlations between complaints during and after competition (p < 0.05). In conclusion, runners of all distances reported a high prevalence of GI and other exercise related complaints. There were some small differences in reporting type and severity of complaints between distances. Results showed small to strong correlations between complaints during and after competition and with nutrient intake, without a clear similar pattern for all distances.